(untitled) (Baghdad Science Journal, 2024)
The alterations in glyoxylate reductase and hydroxy-pyruvate reductase concentrations in the sera and the genetic alterations associated with calcium oxalate kidney stones in Iraqi patients were not studied previously so this study aimed to focus on these points. This study included 80 subjects; they were 50 patients with calcium oxalate stones compared to 30 apparently healthy controls. Biochemical investigations for kidney functions (creatinine, urea, and uric acid), were performed on the sera of both groups. Also, complete blood count, random blood sugar, and blood group tests. Furthermore, urine had been collected for General Urine Examination to visualize oxalate crystals in the urine of the patient. Also, the GRHPR enzyme concentration was measured by ELISA for both groups. The DNA was isolated from whole blood and the target DNA was amplified by PCR then the pathogenic mutations at c.295C>T (rs119490108), c.165G>A (rs180177314) and c.904C>T (p. Arg302Cys) rs180177322 were investigated by direct sequencing of the product, and then the results were analyzed. This study found that the concentration of the enzyme in the controls (4.78 ± 1.06 mg/dl) was significantly higher than its concentration in the patients (0.411 ± 0.02mg/dl). The pathogenic mutations were not found in both studied groups, but other positions were found polymorphic; at exon 4 the rs2768659 (A>G), rs1294628807 (G>A) and rs2736664 (C>T), at exon 6: c.579A>G (p. Ala193=) rs309458 and c.494-68A>G rs309459 and at exon 9 c.*146A>G rs1057507. In conclusion, this study found that calcium oxalate stones were associated with decrease GRHPR enzyme concentration in the patients compared to the control group which may be caused by mutations or epigenetics masking of the gene expression.